AB0854 Effect of tumour necrosis factor alpha inhibitor on serum level of DICKKOPF-1 protein and bone morphogenetic proteins in patients with active ankylosing spondylitis. (23rd January 2014) - Korkosz, M.; Gasowski, J.; Leszczynski, P.; Pawlak-Bus, K.; Jeka, S.; Zalewska, J.; Kwasny-Krochin, B.; Grodzicki, T.
Abstract : Background: Ankylosing spondylitis (AS) is a remodeling arthritis involving axial skeleton, characterized by chronic inflammation and new bone formation (1). The link between inflammation and new bone formation in AS is complex and has not been entirely explained. Current understanding of relationship between inflammation and osteoproliferation is largely based on biomarkers studies which may lead to identification and application of biomarkers specific for bone formation and ankylosis (2). Objectives: To examine changes of serum level of bone remodeling molecules: Dickkopf-1 (Dkk-1), sclerostin, wingless protein-3a and bone morphogenetic protein-7 (BMP-7) during 6 months of anti-TNF treatment in active ankylosing spondylitis (AS) to assess whether inflammation and osteogenesis are coupled. Methods: Forty patients with axial AS were included; 20 with active disease for TNF inhibitor treatment and 20 non-active for non steroidal anti-inflammatory drug treatment. Markers of bone remodeling and inflammation were assessed at baseline and after 6 months. Results: In the TNF inhibitor treated group Dkk-1 significantly decreased from 196.8 pg/ml (95% CI 94.1-399.0) to 116.3 pg/ml (95% CI 38.0-301.6); and BMP-7 significantly increased from 1.4 pg/ml (95% CI 0-23.0) to 20.3 pg/ml (95% CI 4.9-41.3). There was a significant negative correlation between Dkk-1 and BMP-7 at month 6 (r=-0.64; P 0.004) in this group. Non-parametric regression analysis including disease duration, age, sex and baseline CRP confirmed statistically significant effect of treatment on time related changes of Dkk-1 and BMP-7. Erythrocyte sedimentation rate and C-reactive protein as well as Bath Ankylosing Spondylitis Disease Activity Index decreased significantly in anti-TNF treated group. Conclusions: Inflammation and osteoproliferation in active AS with mean disease duration 8, 8 years are coupled. New bone formation in AS occurred if inflammation was successfully depressed. Among the potential biomarkers of bone remodeling Dkk-1 and BMP-7 showed significant time alterations and correlative interactions. References: Braun J, Sieper J. Ankylosing spondylitis. Lancet 2007 Apr 21;369(9570):1379-1390 Maksymowych WP. Biomarkers in spondyloarthritis: From pathophysiology to disease assessment. Joint Bone Spine 2011 Nov 25.doi:10.1016/j.jbspin.2011.09.018 Disclosure of Interest: None Declared